2021
DOI: 10.3390/biomedicines9121752
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Altered Diabetic Myofibroblast Heterogeneity and Gene Expression Are Associated with CD301b+ Macrophages

Abstract: Diabetic wound healing is associated with impaired function and reduced numbers of myofibroblasts, a heterogeneous cell population with varying capacities to promote repair. To determine how diabetes alters myofibroblast composition, we performed flow cytometry and spatial tissue analysis of myofibroblast subsets throughout the healing process in diabetic (db/db) and control (db/+) mouse skin. We observed reduced numbers of profibrotic SCA1+; CD34+; CD26+ myofibroblasts in diabetic wounds five days after injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Pairwise colocalization signals on CD26 and CD29 have been reported in healthy mouse myofibroblasts in the past ( 42 ). Being present in most cell types, CD26 plays a double functionality as an immune-regulatory and proteolytic enzyme.…”
Section: Discussionmentioning
confidence: 78%
“…Pairwise colocalization signals on CD26 and CD29 have been reported in healthy mouse myofibroblasts in the past ( 42 ). Being present in most cell types, CD26 plays a double functionality as an immune-regulatory and proteolytic enzyme.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, the regulation of oxidative stress plays an important role in the wound-repair process. Reduced production of reactive oxidative species (ROS) and/or enhanced antioxidant activity may provide faster wound repair and improve disturbed wound healing processes [41]. Therefore, we aimed to determine if plant-based topical formulations can modulate systemic oxidative status after three weeks of daily application.…”
Section: Discussionmentioning
confidence: 99%
“…High blood glucose activates the advancement of tissue fibrosis, and during diabetic wound healing is linked to reduced and malfunction of myofibroblasts (Deb et al, 2017). To demonstrate the effect of hyperglycaemia on fibroblasts, Haas et al (Haas et al, 2021) noted a decreased expression of fibrosis-related genes and myofibroblasts in diabetic wounds. Lerman et al (Lerman et al, 2003) found a significant reduction in fibroblast cell migration, transformed production of matrix metalloproteinase 9 (MMP-9), and a huge reduction in the production of vascular endothelial growth factor (VEGF) from diabetic mice.…”
Section: Influence Of Hyperglycaemia On Fibroblast Cells During Skin ...mentioning
confidence: 99%